Civil society and competitive authoritarianism in Malaysia - Giersdorf, Stephan; Croissant, Aurel (Journal of civil society, 2011)
This article looks at the development of civil society in Malaysia under competitive authoritarian rule. It focuses on three main questions: What role does civil society play under competitive authoritarian rule? Can it successfully challenge authoritarianism? Or does the existence of a civil society actually strengthen the stability of the authoritarian order? In order to provide answers to these questions, the concept of historical institutionalism will be applied. Thereby, institutional legacies which have been and still are of great influence on the structures and functions of Malaysian civil society will be identified. This study shows that the structures and functions of Malaysian civil society changed significantly over the last five decades. Furthermore, this article argues that civil society groups are increasingly emerging as challengers to the autocratic elites. Nevertheless, the analysis indicates that the institutional framework of competitive authoritarianism heavily restricts civic engagement and the establishment of civic associations. However, the use of coercion and co-optation is restricted due to the regime's competitive character, thus producing a structurally, functionally and operatively limited civil society.
Gesehen am 19.03.2021